Perception of Climate Change Vulnerability and its Impact on Sexual and Reproductive Health and Rights in Khutiya and Banganga River Basins - Poudel, Khusbu; Karki, Sujan; Lamichhane, Kritee; Timilsina, Amit; Dijkerman, Sally; Ghimire, Jagadishwor (Journal of Nepal Health Research Council, 2024)
Background: Nepal is one of the most vulnerable countries to climate change. The drivers of climate risk include its topography, ecological diversity, climatic variability, natural resource dependency, under-development, and socioeconomic vulnerabilities. Climate change affects women and girls in unique ways. Research conducted in Asia Pacific region highlight negative sexual and reproductive health outcomes from climate change-related stressors such as droughts, floods, and air pollution, factors also linked to decreased SRH services utilization, increased maternal mortality rates, and repercussions on women’s mental health. Methods: This is a mixed methods study conducted in two river basins including household surveys with 384 females ages 18-49, 12 focus group discussions, and 22 key informant interviews. We conducted descriptive and thematic analysis. Results: More than half relied on agriculture for income (66%). Despite one-third being heads of households, land ownership was low (13%). Climate change perceptions included rising temperatures (88%), increased heat wave (70%), drying water source (99%), and delayed monsoons (83%), impacting agriculture and increasing women’s workload (61%) due to displacement and male migration. 64% reported disturbances in antenatal and postnatal care visits . Inaccessible healthcare facilities during the rainy season increased maternal mortality risks. Heavy river flooding hindered female community health volunteers access leading to childbirth complications. 82% of women feared being unable to protect their children post-climate events. Moreover, 21% of women faced gender-based violence during or after climate disasters. Conclusions: Our findings suggest clear impacts of climate change on women and the communities. Thus, climate adaptation efforts must be designed to address the unique impacts of the crisis on women and girls, making space for their increased participation and leadership. Keywords: Climate change; gender based violence; malnutrition; migration; sexual and reproductive health and rights.